Reação de híbridos de milho à mancha-de-macrospora - Piletti, Giovani Jian; Casa, Ricardo Trezzi; Bampi, Daiana [UNESP]; Piletti, Ligia Maria Maraschi da Silva; Stoltz, Juan Carlo; Sangoi, Luis; Michelutti, Davi (Grupo Paulista de Fitopatologia, 2014)
Macrospora leaf spot, caused by the fungus Stenocarpella macrospora, has shown to be frequent and important among corn fields in Brazil. Genetic resistance is one of the main strategies to control corn leaf diseases. In Brazil, there is scarce information on the resistance of hybrids to Stenocarpella macrospora. The aim of this study was to evaluate the reaction of 25 corn hybrids to macrospora leaf spot. The experiment was conducted in 2011, in a greenhouse under controlled temperature and relative humidity conditions. Experimental design was completely randomized, with five replicates, each experimental unit consisting of a pot with five plants. Inoculation was done in the V2 growth stage (two fully expanded leaves), and the whorl of each plant received 2.0 mL suspension of 1.8 x 10(4) conidia mL-1 pathogen. The four used fungal isolates were obtained from infected crop residues at the municipalities Lages and Quilombo, Santa Catarina State, and Campinas do Sul and Vacaria, Rio Grande do Sul State. Disease severity was assessed at 21 days after inoculation in the V4 stage (four fully expanded leaves). No tested hybrid was totally resistant to the fungus S. macrospora. There was a significant difference in the disease severity between hybrids and fungal isolates. Hybrids inoculated with Quilombo isolate showed four reaction groups, while the isolates Vacaria, Lages and Campinas do Sul showed two groups. Some hybrids had varied behaviors against the isolates, suggesting different aggressiveness levels. There were hybrids that showed similar reaction to the isolates, suggesting greater stability for macrospora leaf spot.

A mancha-de-macrospora, causada pelo fungo Stenocarpella macrospora, tem se mostrado frequente e importante na cultura do milho no Brasil. A resistência genética é uma das principais estratégias de controle de doenças foliares do milho. No Brasil, são escassas as informações sobre resistência de híbridos à S. macrospora. O objetivo deste trabalho foi avaliar a reação de 25 híbridos de milho à mancha-de-macrospora. O experimento foi conduzido em 2011, em casa de vegetação com condições controladas de temperatura e umidade relativa do ar. O delineamento experimental foi inteiramente casualizado, com cinco repetições, sendo as unidades experimentais constituídas por um vaso com cinco plantas. A inoculação foi feita no estádio fenológico V2 (duas folhas totalmente expandidas), depositando no cartucho de cada planta 2,0 mL da suspensão de 1,8x10(4)conídios mL-1 do patógeno. Foram utilizados quatro isolados do fungo obtidos de restos culturais infectados, oriundos dos municípios de Lages e de Quilombo, Santa Catarina, e Campinas do Sul e Vacaria, Rio Grande do Sul. A severidade da doença foi avaliada aos 21 dias após a inoculação no estádio V4 (quatro folhas totalmente expandidas). Nenhum híbrido testado mostrou-se totalmente resistente ao fungo S. macrospora. Houve diferença significativa na severidade da doença entre híbridos e isolados do fungo. Híbridos inoculados com o isolado Quilombo apresentaram quatro grupos de reação, e os isolados Vacaria, Lages e Campinas do Sul dois grupos. Alguns híbridos se comportaram de maneira distinta frente aos diferentes isolados, sugerindo diferentes níveis de agressividade. Houve híbridos com reação similar entre os isolados, sugerindo maior estabilidade em relação à mancha-de-macrospora.
Resistance of corn hybrids to macrospora leaf spot
Keywords: Diplodia; resistência genética; Stenocarpella macrospora; Zea mays; Diplodia; genetic resistance; Stenocarpella macrospora; Zea mays